Functional compounds in tropical fruit processing by-products and intrinsic factors affecting their composition: A review - María Romero-Martínez; Ricardo Andrade-Pizarro; Claudia De Paula (Current Research in Food Science)
Tropical fruits, highly demanded in the food industry, generate a considerable amount of waste during processing. These traditionally discarded by-products, such as peels, seeds and pomace, are rich in bioactive compounds, natural molecules that have beneficial properties for human health, as they participate in various metabolic processes in the organism. Among the most prominent compounds are flavonoids, carotenoids, phenolic compounds, tannins and vitamin C. Beyond their health benefits, these compounds have significant industrial value and are widely used in the textile, pharmaceutical, cosmetic, biotechnological and food fields, in the latter especially as preservatives, additives, colorants and others. This review explores the main bioactive compounds found in fruit by-products, highlighting their functional relevance and analyzing the intrinsic or fruit-derived factors that influence the composition of these compounds, such as the type of by-product (peels, seeds, bagasse, pomace), the variety of fruit, and the state of maturity at the time of processing. In addition, the extraction methods used to obtain these compounds are addressed, differentiating between conventional techniques, such as solvent extraction, and emerging methods, such as ultrasound-assisted extraction and supercritical fluid extraction, which offer advantages in terms of efficiency and sustainability. The diversity of bioactive compounds and their potential application in various industries highlight the importance of ongoing research in this field. It is necessary to further study the factors that influence the composition of these compounds, as well as the development of more efficient and sustainable extraction methods. These advances will not only add value to food industry waste, but will also contribute to the development of natural products with health benefits.